Perbandingan Nilai Karakteristik Marshall untuk Campuran HRS-WC Menggunakan Material dari Sungai Inbate dan Sungai Bijaesahan - Bela, Krisantos Ria (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Asphalt concrete has become the primary choice for road construction in Indonesia due to its elastic properties suitable for tropical regions. Hot Rolled Sheet-Wearing Course (HRS-WC), as one type of flexible pavement, plays a crucial role in supporting traffic from light to heavy loads. The objective of this study is to compare the Marshall characteristics of HRS-WC mixtures using materials from Inbate river and Bijaesahan river in the East Nusa Tenggara Province. The research method involved testing the material characteristics, mixing HRS-WC, and conducting Marshall method testing. The results indicate that the material from Inbate river exhibits better performance in stability and flexibility compared to material from Bijaesahan river. At the optimum asphalt content of 6.93%, the stability of Inbate river material was 1199.31 Kg, whereas Bijaesahan river was 957.68 Kg. Additionally, the flow of Inbate river material was 4.67 mm, while Bijaesahan river was 3.40 mm. Similar results were observed at the optimum asphalt content of 7.28%, with Inbate river showing stability of 1179.59 Kg and Bijaesahan river 944.16 Kg. The flow of Inbate river material was 4.84 mm, whereas Bijaesahan river was 3.48 mm. These findings demonstrate that material from Inbate river outperforms in stability and flexibility.